SITUS, BUDAYA, DAN STRATEGI PENGEMBANGAN PENELITIAN NEOLITIK DI SULAWESI SELATAN - Nani Somba (WalennaE, 2001)
The most difficult problem in neolitic period analysis is the loss of archaeological context, material resistance, field function transformation and sites damage. Therefore, a strategy is significant to support the research application, such as: priority scale, quality and quantity, finds inventory and detailed location, and lab material analysis availability.